PERANAN REMAJA MASJID AT-TAQWA DALAM MEMBENTUK KARAKTER RELIGIUS REMAJA DIDESA SEI-KANDIS KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Susilo, Riky Pratama; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the desire of researchers to analyze the role of adolescents of the at-taqwa mosque in shaping the religious character of adolescents in the village of Sei-kandis, Pendalian IV Koto District, Rokan Hulu Regency. The formulation of the problem in this study are: How is the role of the At-taqwa Mosque Youth activities in Shaping Youth's Religious Character in Sei-kandis Village, Pendalian IV Koto District, Rokan Hulu Regency. The purpose of this study was to determine how the role of the At-taqwa Mosque Youth Activity in forming the Character of Religi Youth in Sei-kandis Village, Pendalian IV Koto District, Rokan Hulu Regency. The benefit of this research is for adolescents to increase social creativity (in organization) especially in the field of religious knowledge. This research is a qualitative descriptive study carried out in Desa Sei-kandis from June 2019 to November 2019. The population in this study were all mosque youth administrators totaling 23 people with a sampling method in the form of purposive sampling. Data collection techniques used in the form of observation, interviews, questionnaires and documentation. The data analysis technique used is descriptive qualitative. The results of the study: The Role of Adolescents of the At-taqwa Mosque in Shaping Youth's Religious Character in Sei-kandis Village, Pendalian IV Koto District, Rokan Hulu Regency was classified as very good, with a percentage of 69.30%, can be seen from the large percentage of its role that is equal to 51% - 100% = Yes.Key Words: Role, Religious Character, Youth.